Hubungan Antara Penalaran Moral Dengan Academic Dishonesty pada Mahasiswa Fakultas Psikologi UMA - Meganauli Wibowo; Nurmaida Irawani Siregar (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2023)
This paper aims to examine the relationship between moral reasoning and academic dishonesty in psychology faculty students at UMA. The problem is focused on academic dishonesty carried out by students. To approach this problem, the theoretical reference from Anderman Murdock (2007) is used that academic dishonesty is any completeness or assistance that is not allowed to be used in academic tasks and or activities that interfere with the assessment process. Data were collected using a Likert scale model with two scales, namely the moral reasoning scale and the academic dishonesty scale which were compiled by researchers and analyzed quantitatively. The results of the study using the product moment cotellation technique showed that there was a significant negative relationship between moral reasoning and academic dishonesty with an rxy value of -0.589 and p = 0.000. The results of this study conclude that the higher the academic dishonesty that is carried out, the lower the moral reasoning possessed by students and according to the results of the data analysis carried out, it is known that the students' moral reasoning is low and the academic dishonesty of students is high.